2021
DOI: 10.3166/phyto-2021-0281
|View full text |Cite
|
Sign up to set email alerts
|

Composition chimique et bioactivité de l’huile essentielle des feuilles de thuya de Berberie (Tetraclinis articulata Vahl) et de ses fractions chromatographiques

Abstract: L'huile essentielle des feuilles de Tetraclinis articulata Vahl Masters et ses fractions obtenues par fractionnement de type flash sont analysées par GC et GC/MS. L'huile essentielle totale des feuilles est constituée de l'acétate de bornyle (30,6 %), le camphre (18,6 %), l'α-pinène (16,8 %), le limonène (5,7 %) et le bornéol (4,7 %) comme composés majoritaires. Le fractionnement de l'huile a donné une fraction hydrocarbonée (FH) et trois fractions oxygénées FO1, FO2 et FO3. La fraction FH est constituée d'hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It has been used as a diuretic, antipyretic, anti-rheumatic and oral hypoglycemic (Bellakhdar et al, 1982;Ziyyat et al, 1997). In parallel, various biological activities have been reported for extracts and essential oils (seeds, leaves, aerial parts) such as cytotoxic (Buhagiar et al, 1999;Aouinty et al, 2006), vasorelaxant (Zidane et al, 2014), antimicrobial (Bourkhiss et al, 2007a;Abi-Ayad et al, 2011;Chikhoune et al, 2013;Djouahri et al, 2016;Ben Ghnaya et al, 2016;Ibrahim et al, 2017;Rabib et al, 2019;2020), antioxidant and anti-inflammatory activities (Bourkhiss et al, 2010;Djouahri et al, 2013). The antimicrobial activity of T. articulata essential oil has been the subject of a many studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used as a diuretic, antipyretic, anti-rheumatic and oral hypoglycemic (Bellakhdar et al, 1982;Ziyyat et al, 1997). In parallel, various biological activities have been reported for extracts and essential oils (seeds, leaves, aerial parts) such as cytotoxic (Buhagiar et al, 1999;Aouinty et al, 2006), vasorelaxant (Zidane et al, 2014), antimicrobial (Bourkhiss et al, 2007a;Abi-Ayad et al, 2011;Chikhoune et al, 2013;Djouahri et al, 2016;Ben Ghnaya et al, 2016;Ibrahim et al, 2017;Rabib et al, 2019;2020), antioxidant and anti-inflammatory activities (Bourkhiss et al, 2010;Djouahri et al, 2013). The antimicrobial activity of T. articulata essential oil has been the subject of a many studies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the antimicrobial activity of the essential oil isolated from leaves of T. articulata was evaluated against Staphylococcus aureus, Escherichia coli and Aspergillus flavus. A high activity was observed, with minimal inhibitory concentrations varied between 1/500 and 1/5000 (Bourkhiss et al, 2007a). Chikhoune et al in 2013 reported the antimicrobial activity of leaf essential oil samples of T. articulata collected from two different locations in Algeria.…”
Section: Introductionmentioning
confidence: 99%